2020
DOI: 10.1016/j.jclepro.2020.122283
|View full text |Cite
|
Sign up to set email alerts
|

Whole system valuation of arable, agroforestry and tree-only systems at three case study sites in Europe

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 62 publications
1
25
0
7
Order By: Relevance
“…The policy scenario demonstrated that at the current payment level, regional biodiversity was considerably degraded as grassland and in particular, orchard meadows were often replaced by crop production. This implies that crop production in Switzerland is highly financially attractive if subsidies are considered (Giannitsopoulos et al, 2020). Farmers receive a guaranteed payment of 1,400 CHF/ha for crop production as well as 120 CHF/ha as price support for supplying cereals (Bundesrat, 2013), while a guaranteed premium for cultivating grassland is 1,000 CHF/ha in the hilly regions (Bundesrat, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The policy scenario demonstrated that at the current payment level, regional biodiversity was considerably degraded as grassland and in particular, orchard meadows were often replaced by crop production. This implies that crop production in Switzerland is highly financially attractive if subsidies are considered (Giannitsopoulos et al, 2020). Farmers receive a guaranteed payment of 1,400 CHF/ha for crop production as well as 120 CHF/ha as price support for supplying cereals (Bundesrat, 2013), while a guaranteed premium for cultivating grassland is 1,000 CHF/ha in the hilly regions (Bundesrat, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not consider their non-market benefits, i.e., externalities such as reduced soil erosion risk, carbon sequestration or regional identity in the calculation of the economic profit. Although capturing the real value of orchard meadows is a core challenge in the economic assessment (Schönhart, et al, 2011a), accounting for such non-market benefits of orchard meadows in the decision process will improve the validity of results and help to determine a more appropriate level of financial support (Bethwell et al, 2021;Giannitsopoulos et al, 2020).…”
Section: Methodological Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, a range of provisioning, regulating and cultural ecosystem services are provided by the environment, many of which are non-market benefits. Previous research has shown that tree-based systems can provide important benefits relative to arable systems, for example, in terms of regulating ecosystem services (e.g., soil erosion control, nutrient reduction in water, air quality improvement) [51,52] and cultural ecosystem services (e.g., recreation, aesthetics and sense of place) [53,54]. The value of these benefits for society needs to be incorporated in cost-benefit analysis studies to provide an improved basis for valuing land use systems.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation is especially apparent for temperate regions while more research has been conducted in the tropics. The number of experiments in temperate regions, however, is growing, with newly designed studies, but it will take several years to decades until the trees planted are mature enough to enable detailed investigations of the long-term system effects [13].…”
Section: Introductionmentioning
confidence: 99%